"Some Vital Religion": Social Religion and the Science of Character Education in the United States, 1918–1932. (23rd December 2021) - McCamant, Jane
Abstract: The history of American public education has generally been considered as a steady transition from religious and sectarian to secular and pluralist, with the role of science in education increasing as the role of religion decreased. This article examines a conception of the role of religion in education that does not fit this narrative, the "social religion" of theorists of moral and character education in the 1920s. Relying on ideas of religious naturalism and with an orientation toward the practical effects of religious belief, this community of scholars asserted a concept of religion that would allow it to be at the heart of the common school project, uniting all under the common morality of the social good. Influenced both by liberal Protestant humanism and the scientific worldview pervasive in education reform at the time, these character educationists' ideas remind us of the historical contingency of categories like "religious" and of the antiquity of ideas we might classify under the heading of spirituality in American culture.